Projeto e análise de inversores cuk integrados com operação unidirecional e bidirecional - Inoue, Rafael Takeshi (2025)
This work presents a new single-phase bidirectional integrated Cuk inverter (BICI) for DC microgrid interface between DC sources and AC bus. Aditionaly, this work also proposes two new possibilities of operation of the single-phase unidirectional integrated Cuk inverter (UICI). Being: i) The application of a multi-resonant ontroller together with a PI controller (PI-MR) to the ICIU; ii) Proposal of a high frequency modulation (UICI-HF), which allow an improved dynamics to the UICI. The UICI with the muti-ressonant compensator is designed to operate as a interface converter between DC sources and off-grid AC loads, meanwhile the UICI-HF designed to operate in stand-alone mode and grid-connected. These integrated inverters are formed from the junction of the Cuk DC-DC converter and the single-phase voltage source inverter. Both converters UICI and BICI are esigned to operate in discontinuous conduction mode since it presents linear static gain and improved system requency response, which facilitates the implementaion of a control loop for a given frequency bandwidth. These converters also have similar requency respose to the DC-DC Cuk converter. This work present a qualitative and quantitative analisys of the structures, including steady state analisys, small signal modeling and the compensator design. The UICI and BICI were evaluated through computational simulation in MATLAB/Simulink and experimentally. The UICI and UICI-HF were evaluated for three scenarios: i) resistive load; ii) resistive load step; iii) and nonlinear load. The PI-MR showed improvements when compared to the PI compensator, lowering from 7.4% to 4.4% the THD for the third scenario. Meanwhile, the UICI-HF showed improved dynamics in comparison with the UICI, which was capable of supply sinusoidal voltage to the nonliner load with 3,8% with only a PI compensator. And finally, the bidirectional operation of the BICI was evaluated, in which the current in both directions of power flow presented THD lower than 2.2%. The BICI was capable of grid forming while the AC current presented 4.4% of THD.